2012
DOI: 10.1111/j.1525-1594.2011.01416.x
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Analysis to Determine Shear Stresses and Rates in a Centrifugal Left Ventricular Assist Device

Abstract: Axial flow left ventricular assist devices (LVADs) are a significant improvement in mechanical circulatory support. However, patients with these devices experience degradation of large von Willebrand factor (vWF) multimers, which is associated with bleeding and may be caused by high shear stresses within the LVAD. In this study, we used computational fluid mechanics to determine the wall shear stresses, shear rates, and residence times in a centrifugal LVAD and assess the impact on these variables caused by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…†Present peak value in typical devices based on experimental measurements and computational fluid dynamics calculations (blood flow rate was 4-7 L/min). These values were summarized from Girdhar et al, 75 Selgrade and Truskey, 76 and Fraser et al 77 This delayed recovery is also demonstrated in the long relaxation time of VWF fibrils returning back to their original conformation after a mechanical force applied to induce domain-unfolding was removed. 52,81 A shear stress of ;8 Pa is also necessary for VWF selfassociation in solution as measured using light-scattering.…”
Section: Regulation Of Vwf By Physical Forcesmentioning
confidence: 97%
See 3 more Smart Citations
“…†Present peak value in typical devices based on experimental measurements and computational fluid dynamics calculations (blood flow rate was 4-7 L/min). These values were summarized from Girdhar et al, 75 Selgrade and Truskey, 76 and Fraser et al 77 This delayed recovery is also demonstrated in the long relaxation time of VWF fibrils returning back to their original conformation after a mechanical force applied to induce domain-unfolding was removed. 52,81 A shear stress of ;8 Pa is also necessary for VWF selfassociation in solution as measured using light-scattering.…”
Section: Regulation Of Vwf By Physical Forcesmentioning
confidence: 97%
“…76,77 Regions of high, nonphysiologic flow are formed in axial pumps with an estimated wall shear stress of .10 Pa, as is found in most of the devices. 76,78 However, a recent study that compared the performance of centrifugal and axial-flow LVADs in 102 patients showed an equivalent loss of large VWF multimers and similar incidences of bleeding and thromboembolic events. 79 A growing body of evidence suggests that a local shear stress in excess of 10 Pa can result in the application of forces .…”
Section: Regulation Of Vwf By Physical Forcesmentioning
confidence: 98%
See 2 more Smart Citations
“…While baseline, preramp imaging is important for device screening, clinical suspicion for thrombus should guide the decision for further testing as speed manipulation creates transient variation in an otherwise continuous flow state, leading to fluctuations in shear strain force [8]. We postulate that this may amplify hemorheological factors such as heat production, platelet activation, and turbulence, which are already recognized as contributory to thrombus formation in LVAD patients [9].…”
Section: Discussionmentioning
confidence: 98%